Study of the effect of different drug treatment strategies in patients with hypertension - Rekovets , Oksana; Sirenko , Yuriy; Progonov , Sergey (The Ukrainian Scientific Medical Youth Journal, 2024)
fixed combinations of antihypertensive medications can improve blood pressure (BP) control, reduce complications and increase life expectancy. The objective of our study was to analyze the efficiency of fixed, free and not traditional combinations of antihypertensive medications in the management of patients with arterial hypertension. 396 patients with hypertension with various degrees of its severity were examined. The inclusion criteria were the age of patients older than 18 years and the level of office BP greater than 140/90 mm Hg. Patients were in three observational groups: traditional free combinations, traditional fixed combinations, and not traditional free combinations. 91 patients received an unfixed combination of ramipril and hydrochlorothiazide. 132 patients received an unfixed combination of metoprolol-retard and hydrochlorothiazide. 50 patients were assigned to group with studying the effect of fixed traditional double and triple combinations of antihypertensive medications. The last 123 patients with hypertension comprised the group of studying the effect of dihydropyridine and non-dihydropyridine calcium blockers on the degree of BP reduction and the development of adverse events. The use of metoprolol-retard 100-300 mg per day in patients with mild to moderate hypertension provided a significant decrease in office BP: SBP/ DBP – 32/18 mm Hg, heart rate (HR) - 18 bpm, ABPM: 24SBP/DBP – 21/13 mm Hg and HR - 7 bpm. Achievement of the target BP 93.6% office BP and in 84,9% - ABPM. The use of ramipril 10 mg in combination with hydrochlorothiazide 25 mg in patients with mild and moderate arterial hypertension provided a reliable reduction of both office SBP/DBP - 36,6/17,2 mm Hg and ABPM 24SBP/DBP - 18,9/7,0 mm Hg. The prescribed monotherapy of lercanidipine 20 mg or a low-dose combination of lercanidipine 10 mg and diltiazem 120 mg were most effectively tolerated treatment. Combined treatment based on lercanidipine and diltiazem had similar efficiency as treatment based on monotherapy with lercanidipine, according to both office and ABPM measurements. Patients taking fixed triple combination of valsartan/hydrochlorothiazide/amlodipine had decrease 24SBP/DBP - 23.8/20.7 mmHg (p<0,05). This improvement of BP on this combination was also observed during the day and night period - 27.4/22.6 mmHg and 20.5/18.2 mm Hg, respectively (р<0.05). Achieved the target blood pressure during ABPM was 77.3% in the group of fixed double therapy valsartan/amlodipine and 95.2% in the triple combination valsartan/amlodipine/hydrochlorothiazide. The triple fixed combination of valsartan/ hydrochlorothiazide /amlodipine was the most effective in lowering blood pressure according to data of office measurement and 24 hours monitoring. It contributed to the achievement of target blood pressure levels at office measurement - 95.7% and at ABPM - 95.2%.